Modified double-row suture bridge technique for anterior colliculus fractures combined with deltoid ligament injury: a retrospective study - Jianlong Ni; Zhihao Chen; Wang Wei; Ruiying Li; Dazhi Wang; Dongjian Wang; Zenan Tian; Zhikun Jia; Qichun Song; Meng Feng; Zhibin Shi (BMC Musculoskeletal Disorders)
Abstract Background The management of anterior colliculus fractures in combination with deltoid ligament injuries is a topic of debate, and there is a need to improve surgical outcomes. The purpose of the present study was to describe the application of a modified double-row suture bridge technique and evaluate its early clinical outcomes in the management of anterior colliculus fracture combined with deltoid ligament injury. Methods From 2020 to 2022, 12 patients with anterior colliculus fracture combined with deltoid ligament injury were treated using a modified double-row suture bridge technique. For clinical outcome evaluation, objective data are presented through clinical examination findings; radiographic assessments, including X-rays and computed tomography (CT); and follow-up analysis utilizing American Orthopaedic Foot & Ankle Society ankle‒hindfoot (AOFAS) scores, Olerud Molander Ankle Scores (OMAS), and visual analogue scale (VAS) scores. Preoperative and follow-up scores were compared with Student’s t test. (p < .05). Results The mean age of the patients was 52.67 ± 9.42 years (range: 39–74). The mean duration of follow-up was 14.42 ± 1.51 months (range: 12–17). At the final follow-up, the mean AOFAS score (P < 0.001) improved to 91.50 ± 2.65 points (range: 87–96), the mean OMAS (P < 0.001) improved to 77.08 ± 3.97 points (range: 70–85), and the mean VAS score (P < 0.001) improved to 0.25 ± 0.45 points (range: 0–1). Nine patients achieved excellent outcomes, and three achieved good outcomes according to the AOFAS score. Follow-up imaging evaluation indicated satisfactory alignment of the fracture and complete healing. Clinical examination suggested good mobility of the ankle. At the last follow-up, ankle dorsiflexion mobility was 14–18 degrees, plantar flexion mobility was 42–45 degrees, inversion mobility was 27–32 degrees, and eversion mobility was 22–25 degrees. Conclusions The modified double-row suture bridge technique is effective for achieving anatomic reduction of anterior colliculus fractures, and the technique also provides substantial benefit to the injured deltoid ligament. With this technique, the clinical outcomes can be significant and encouraging, indicating a new stage in its application and development.